Thematic repertoire of feuilletons about the New Poet and its diachronic transformations - E. I. Vozhik; R. A. Lisiukov (Шаги)
The article discusses the thematic range of feuilletons featuring the New Poet published in the Sovremennik magazine between 1847 and 1862, as well as the changes in their thematics over time. An analysis of the content of these feuilletons shows that their authors, including Ivan Panaev, were well aware of the existing tradition of the feuilleton genre and at first adhered to its conventions. However, over time, they moved away from conventional, genre-specific approaches to selecting feuilleton topics and adapted the notes about the New Poet to current events. The feuilleton authors of Sovremennik sought to develop an idealized image of a writer who represented the project of a new literature during the last years of the reign of Nicholas I, as who was an active member of society during the Great Reforms era — a person familiar with contemporary public debates. In addition, Panaev and his co-authors rely on the gradual expansion of the thematic diversity in the feuilleton genre, trying to orient the reader in a larger context of events and perspectives. The main methods used in the article are structural topic modeling, which highlights broad subject-semantic fields, as well as assessment of information entropy that indicates the degree of diversity in the feuilleton themes.